CRITICISM OF ISLAMIC CRIMINAL LAW AGAINST ARTICLE 5 OF THE UNIVERSAL DECLARATION OF HUMAN RIGHTS RELATED TO THE APPLICATION OF QISHASH PUNISHMENT - Salsabila, Adzanah Mariska; Faizal, Enceng Arif; Najmudin, Deden; Pahlevi, Mohamad Syahreza (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Abstract The application of qishash punishment in Islamic criminal law is often debated because it is considered to be contrary to Article 5 of the Universal Declaration of Human Rights (UDHR), which rejects all forms of cruel, inhuman, and degrading punishment. This accusation is certainly misleading because it views qishash only from a symbolic-artificial perspective. The purpose of this study is to interpret Article 5 of the UDHR, analyze the concept of qishash punishment in fiqh jinayah, and critique Article 5 of the UDHR in relation to the application of qishash punishment. This study uses qualitative research with a normative juridical method through a statute approach, conceptual approach, and comparative approach through library research on primary and secondary legal sources, which are then critically analyzed. The results of this study are able to criticize Article 5 of the UDHR with two main arguments, namely, first, qishash is not a cruel, inhuman, and degrading punishment; second, there is caution in the application of qishash punishment through various critical theories and logic (evotivism theory, deconstruction theory, logical fallacy, cultural relativism theory, critical human rights theory, and postcolonial theory). The novelty of this research lies in its attempt to critique the human rights perspective on the application of qishash punishment by offering a maqashid al-syari'ah qishash approach, namely qishash as a mechanism for protecting the right to life (hifz al-nafs) as well as a form of substantive and proportional justice. The academic contributions of this research include enriching the study of Islamic criminal law with an integrative perspective, offering a critical analysis of the interpretation of Article 5 of the UDHR, and providing normative references for the development of a more contextual national criminal law.